THE ANALYSIS OF GENERATION Z’S CONSUMPTIVE BAHAVIOR TOWARD APPAREL PRODUCT IN MANADO - Rakian, Sintia Melany; Lapian, Joyce S.L.H.V.; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: Generation Z is the next generation after millennial generation. This generation is the people who were born in the period from 1995 to 2010 and grew up with technology, internet and social media. Born and developing in the era of digital technology makes generation Z a technology addicts and tends to be anti-social. Therefore, they are studied by researchers and marketers to determine the generation characteristics as they have a lot of influence over the older generations and are trendsetters across all industries. The aim of this research is to find out if price and social media affect generation Zâ€™s consumptive behavior on buying apparel product. This study used a sample of 100 students of generation Z as university student in Manado especially at Faculty of Economic and Business at Sam Ratulangi University and the data was collected by using Google form. This study used a quantitative research method with Multiple Linear Regression (MLR) as a statistical technique. The conclusion shows that before they buy products with social media, it turns out that they have an effect on generation Z for consumptive behavior. For recommendation generation Z are expected to be able to learning about financial literacy.Â Keywords: generation Z, price, media social, consumptive behavior